Determination of the Appropriate Plasticity Hardening Model for the Simulation of the Reverse Bending and Straightening of Wires for Civil Engineering Applications (Global Journals of Research in Engineering, 2013)
The industry requires an understanding of the effects of reverse bending and straightening test wires for civil engineering applications undergo to detect laminations in them on their tensile properties In this paper the identification of the appropriate plasticity hardening model for the simulation of wires reverse bending and straightening test which involves double strain reversal is presented Finite element simulations revealed that the isotropic hardening model predicted a continuous work hardening of the wire during the bending reverse bending and straightening operations and did not capture the softening of the wire due to the Bauschinger effect Conversely the combined hardening model adequately captured both the work hardening and Bauschinger effect that are associated with the reverse bending and straightening processes Consequently it is demonstrated that the combined hardening model is the appropriate plasticity hardening model for the simulation of reverse bending and straightening of carbon steel wires used for civil engineering applications This paper thus established the appropriate plasticity hardening model required for the FE simulation of the wires reverse bending and straightening test needed to investigate the effects of reverse bending and straightening test on the tensile and fracture properties of a typical wire used for civil engineering applications
Keywords: bauschinger effect; combined hardening; finite element simulation; isotropic hardening; laminations; reverse bending strain reversal wires